Sei sulla pagina 1di 25

Q = N q e

N Z + q e

[Q] =

 q e = −1,60 × 10 −19 q p = +1,60 × 10 −19

m e = 9,11 × 10 31

m p

= 1,67 × 10 27

q 1 q 2

F = K 0 q 1 q 2 uˆ

r 2

1

K 0 = 4πε 0

= 9,00 × 10 9 2 2

ε 0 = 8,854 × 10 12 2 2

E

E =

F 0

q 0

q 0

 q 0 > 0 ⇒ E ↑↑ F 0 E = F 0

q 0

[E] =

N

C

E

Q

q 0

E = K 0

Q

r 2

E =

F

q

0

0

=

K 0 Q q 0

r 2

q

0

E = K 0 Q 2 uˆ

r

uˆ

E

E

= E 1 + E 2 + E 3 + ··· +

E

n

E = K 0

q

r

1

2

1

uˆ 1 + q 2 uˆ 2 + q 3 uˆ 3 + ··· + q n

r

2

2

r

2

3

r

2

n uˆ n

E

dq

d E = K 0 dq uˆ r

r

2

d E = K 0 dq uˆ r

r

2

E = K 0 L,A,V

dq

r

2

uˆ r

q 1 = 1 × 10 6

q 2 = +3 × 10 6

q 1 r 12 = 15 r 13 = 10 ϕ = 30 o

q 3 = +2 × 10 6

0,2 l = 10 β = 30 o

q 1 = +8 × 10 6

20

q 2 = 8 × 10 6

E

q 1 = 25 µ q 2 = 16 µ q 3 = 8 µ

 q 1 C

q 1 = 10 µ q 2 = 18 µ q 3 = 12 µ

 q 1 R

l +q a

+q a x

E

 E −→ E −→

(Q) (q)

q

q

F = q E

(+) =

() =

F

F

↑↑ E

↑↓ E

 F

F = q E

E q

F :

F = m a

a =

F

m = q m

E

m

2 1 a x t 2

x = x 0 + v 0x t +

1

y = y 0 + v 0y t + 2 a y t 2

v x = v 0x + a x t

v y = v 0y + a y t

2 × 10 7 2 × 10 4

3500

v 0

5 × 10 8

= 3 × 10 6

60 o

 e = 1,60 × 10 −19 m = 9,11 × 10 −31